Evaluation of Apelin, Elabela, and Certain Biomarkers in Patients with Metabolic Disease Associated with Obesity - Layla Imad Ali; Shaimaa Imad Ali; Fayhaa M. Khaleel; Wasan Saher Hassan; Kawther Adeeb Hussein; Great Iruoghene Edo (Diyala Journal of Medicine, 2025)
Background: A novel peptide known as Elabela was recently discovered; it functions similarly to apelin and acts through apelin receptors. This research is to compare the characteristics and biological roles of apelin and Elabela in patients with metabolic syndrome who are obese and those who are not. Patients and Methods: A cross-sectional study included 90 participants, ages 20–45, whose samples were collected from Al-Yarmouk-Hospital/Al-Karkh/Baghdad, from April–July/2024. Classified into three groups: group1 was obese metabolic syndrome patients (N=30), group 2 was metabolic syndrome patients without obesity (N=30), and group 3 was control (N=30). Anthropometrics and parameters were assessed for all study groups. Fasting blood glucose levels and lipid profiles were determined using an enzymatic process with spectrophotometric methods, while insulin, apelin, and Elabela were evaluated by enzyme-linked immunosorbent assay. Results: The result shows a significant difference in Body Mass Index, Waist to Hip Ratio, Lipid profile, FBS, apelin, insulin, and HOMA-IR, while there was no significant difference between the study groups in Elabela levels. In addition, there is a positive correlation between apelin and BMI, FBS, and insulin. apelin levels have a higher diagnostic value for obesity than metabolic syndrome, respectively. Conclusion: This study suggests that apelin and Elabela are powerful modulators of the metabolism of adipose cell and highlights the crucial role of apelin in MetS in both non-obese and obese MetS, as well as in clinical and biochemical markers associated with obesity. Keywords: Apelin, APJ, Elabela, Metabolic Syndrome, Obesity.